Alterations in lymphocyte phenotype and function in children with shigellosis who develop complications. - Azim, T (1996)
This study was designed to see whether alterations occur in peripheral blood mononuclear cell phenotype and function in children with Shigella dysenteriae 1 infection with complications (leukemoid reaction and/or hemolytic-uremic syndrome) and whether there are any alterations prior to the development of complications. The following groups of children (ages, 12 to 60 months) were compared: children without any infection (n = 51), children with uncomplicated shigellosis (n = 65), children admitted with complicated shigellosis (leukemoid reaction and/or hemolytic-uremic syndrome) (n = 29), and children with shigellosis who developed complications after enrollment (subsequently complicated shigellosis) (n = 12). Tests for the peripheral blood mononuclear cell phenotype (CD3, CD4, CD8, CD57 [corrected], CD20, and CD25), spontaneous proliferation, and the proliferative response to phytohemagglutinin, pokeweed mitogen, and the lipopolysaccharide of S. dysenteriae 1 were performed, as were skin tests for delayed-type hypersensitivity (DTH). Children who subsequently developed complications differed from other groups of children as follows: (i) the numbers of CD3+ and CD4+ cells were lower than in uninfected children (P < 0.05), (ii) the CD4/CD8 ratio was lower than in children with uncomplicated shigellosis (P < 0.05) and in uninfected children (P < 0.05), and (iii) the levels of spontaneous proliferation of peripheral blood mononuclear cells were higher and DTH responses were lower than those in children with uncomplicated shigellosis (P < 0.05 and P < 0.017, respectively). Children with complications differed by having (i) increased numbers of CD3- CD57- [corrected] CD20- cells (P < 0.05) compared with those in other groups of children and (ii) lower CD4/CD8 ratios (P < 0.05), higher levels of spontaneous proliferation (P < 0.05), and lower DTH responses (P = 0.005) than children with uncomplicated shigellosis. Three to five days after enrollment, the number of CD4+ cells increased in children who subsequently developed complications (P = 0.025), i.e., when they developed complications and at this time their CD4+ cell number was similar to that of other groups of children. Thus, lymphocyte phenotype and function are altered prior to the development of complications in children with shigellosis, and once complications develop, the pattern of alterations changes. Whether these alterations have a role in precipitating complications or whether they reflect early events underlying the development of complications remains to be elucidated.